'Your Girls That You All Love Are Mine Already': Criminal Female Sexuality in Bram Stoker's Dracula. Issue 1 (1st May 2016) - Shane, Beth
Abstract : This essay considers how Bram Stoker's Dracula (1901) engages both contemporary medical models and common-sense conceptions of female criminality and sexuality. From Dracula, the figure of Lucy Westenra emerges as a quintessential femme fatale. Lucy's neck bears the characteristic marking of the vampire, but we never witness the bite; as a result, ambiguity surrounds the causal relationship in the process of becoming a vampire. The novel produces this ontological ambiguity to perpetuate and to exacerbate contemporary views regarding the radical instability of female nature. Under this logic, Lucy's encounter with the vampire brings only latent impulses to the surface. Stoker's narrative exploits this physiological uncertainty to perpetuate the sensational terror that all female sexuality is monstrous, threatening to render the British man a debased specimen of his former glory. By tracking the various logical ellipses and rhetorical slippages which give shape to Stoker's female vampires, I demonstrate how Stoker's novels enact the same anxious rhetoric that likewise informs the portrait of female sexuality in nineteenth-century sexology.